If it's not what You are looking for type in the equation solver your own equation and let us solve it.
25y+5=23y-7
We move all terms to the left:
25y+5-(23y-7)=0
We get rid of parentheses
25y-23y+7+5=0
We add all the numbers together, and all the variables
2y+12=0
We move all terms containing y to the left, all other terms to the right
2y=-12
y=-12/2
y=-6
| 27y+7=25y+5 | | -4(2x+1)=-4(-5+x) | | 5m-7=-(m+5)-5 | | 6n–7n–=4+n | | 3(-6-5x)=-3-3(3x+1) | | 3(-6-5x)=-3-3(3x+1 | | 4x+3=7;x= | | 3x+-5=2x+1 | | X+7=-x+10 | | -8b-8(4b-3)=-6(6b+4) | | 3m/2/5m=2/3 | | 3t+11=8t-9 | | 7x^2+224=-84x | | y=3+60 | | 4(x-4)+8(4x+2)=36 | | y=3+42 | | 8a-22=5a-7 | | y=3+36 | | -4=-4x=12 | | y=3+30 | | 7x^2-5=51 | | -72=6(-3+8x)-3(-8+3x) | | y=21-12 | | 13p+85=2p+96 | | y=21-10 | | (2x–3)+(5x–6)=180 | | 19b+90=15b+98 | | y=21-8 | | (2y–3)+(5y–6)=180 | | 2(2x+4)=-18 | | y=21-6 | | 36=-(n-3)+3(n+7) |